PORTARIA PRPB Nº 288, DE 25 DE JULHO DE 2017. - Rodolfo Alves Silva (DMPFe, Administrativo de 31/07/2017, p. 26., 2017)
Dispõe sobre o horário de expediente na PR/PB nos dias 27 e 28 de julho de 2017.